ZC3H18 regulates alternative splicing and related genes in cervical cancer - Chen, Wenjuan; Liu, Chenying; Li, Siyi; Xie, Xingyun; Hu, Dan; Lin, Yaobin (Frontiers in Genetics, 2025)
IntroductionAlternative splicing (AS) and RNA-binding proteins (RBPs) have been implicated in various diseases. However, a comprehensive understanding of their role in RNA metabolism, progression, and metastasis in cervical cancer remains elusive. This study aimed to identify the potential effect of zinc finger CCCH-type containing 18 (ZC3H18) in cervical cancer.MethodsThe Gene Expression Omnibus (GEO) dataset (GSE94427) was used to analyze the expression level of ZC3H18 in HeLa cells and its regulated alternative splicing events (ASEs). The Cancer Genome Atlas (TCGA) cervical cancer dataset and in vitro experiments were used for verification. The signaling pathways and functions of ZC3H18-regulated ASEs were investigated through enrichment analysis.ResultsKnockdown of ZC3H18 in HeLa cells increased the expression of 106 genes but decreased the expression of 226 genes. ZC3H18 was found to be involved in the regulation of 1,830 ASEs. The AS genes were enriched in cervical cancer-related signaling pathways. Validation using 39 cervical cancer samples from the TCGA database showed that 20 cases had low ZC3H18 expression and 19 had high expression. By integrating GEO and TCGA datasets along with in vitro experiments, 18 ASEs with consistent changes were identified.DiscussionThis study demonstrated that ZC3H18 extensively regulates AS of cancer-associated pathways in HeLa cells and cervical cancer tissues. The identification of ZC3H18-regulated ASEs may provide potential targets for cervical cancer treatment.